2012
DOI: 10.4236/ojrad.2012.21003
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of MRI in Primary Cervical Cancer

Abstract: Introduction: Magnetic resonance imaging (MRI) studies obtained during the initial staging of patients affected by uterine cervical cancer were compared to the final histological report after surgery. Methods: Data were retrieved from published papers. Results: MRI detection of lymph node metastases shows a sensitivity of 49.3% (1209 patients) and a specificity of 87.7% (1182 patients). Parametrial involvement detection has 66.2% sensitivity (1288 patients) and 83.6% specificity (1282 patients). MRI tumor size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…MRI has limited value in the differentiation of metastatic lymph nodes from hyperplasia, in detecting microinvasion in nonenlarged lymph nodes, and for the evaluation of cervical stroma [26, 27]. The limitation in the evaluation of primary tumour size in MRI also includes the impossibility of margin definition, confusing with peritumoral reactions or scars and small tumours (< 1 cm), which might be only visualised on early dynamic contrast-enhanced sequence (DCE) MRI as enhanced foci [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…MRI has limited value in the differentiation of metastatic lymph nodes from hyperplasia, in detecting microinvasion in nonenlarged lymph nodes, and for the evaluation of cervical stroma [26, 27]. The limitation in the evaluation of primary tumour size in MRI also includes the impossibility of margin definition, confusing with peritumoral reactions or scars and small tumours (< 1 cm), which might be only visualised on early dynamic contrast-enhanced sequence (DCE) MRI as enhanced foci [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…But they also say that MRI is much better for myometrial and endometrial involvement and is not sensitive enough to replace histopathology. (8) In some studies MRI has shown better accuracy than clinical examination. (9) LIMITATIONS: Since MRI has definite advantage over CT, comparison would have been ideal between MRI and clinical examination.…”
Section: Parametrial Involvement Numbermentioning
confidence: 99%
“…The development of medical technology in recent decades, especially imaging technology, created a paradigm of imaging technology as a vital part of cancer management. In 2018, FIGO had revised its guidelines of cervical cancer, recommending imaging modalities as an additional examination to further guide clinician in diagnosis and treatment choice 7,8 .…”
Section: Introductionmentioning
confidence: 99%